Melancholy Left and Spectral Utopianism [la Melancolía de Izquierda y el Utopismo Espectral] - Retamal-Hernandez, C (Universidad Pontificia Comillas de Madrid, 2016)
From a review of Walter Benjamin discussed I) the notion of "left melancholy" to describe the emotional state of the heirs of Marxism. To do II) explores how the romantic melancholy is sublimated in Marxism. Then how this melancholy returns overshadowing his utopian impulse. III) After the paradoxes of some representations of melancholia are analyzed to show the religious tensions in utopianism and how these are transferred to the worldview of the left. IV) This analysis shows, from a psychoanalytic point of view, the need to consider the death of the "equivalent abstractions" own melancholy, to find out what is it that has died in leftist thought. Finally V) the way it is conceived and developed strong subjetivad in modern culture is observed is the basis of melancholy left and it is the exit of such a condition.
Keywords: Marxism; Walter Benjamin; Durer; modernity; subjectivity